PREVENTION OF PRISONERS COMMITTING VIOLENCE IN PRISON - Prabowo, Rizky Setyo (Department of Guidance and Counseling, FIP, Undiksha, 2020)
The purpose of this study is to find out what preventative measures to prevent violence between convicts in existing correctional institutions. Penitentiary has a very strategic role in the framework of developing human resources, the implementation of guiding convicts including how conducive conditions are created in their implementation. The method used is normative and empirical juridical methods, namely research emphasizing secondary data by studying and reviewing riot prevention efforts, especially positive legal rules derived from library materials that exist in the legislation regulations, namely Law No. 12 of 1995 concerning Corrections and other related laws. This study uses descriptive analysis research, which is a study that describes and describes the situation or facts that exist about efforts to prevent violence between prisoners in prison and detention centers in Indonesia. The results of this study are known that in correctional institutions the reality is constrained by several things such as, inadequate prison facilities and detention centers, the number of employees or officers who are not in accordance with the number of convicts, the number of convicts that exceeds capacity, the lack of supervision also caused an easy commotion inside the correctional institutes and detention center.